2022
DOI: 10.1155/2022/1211499
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Role of Radiology and Laparoscopy in Childhood Peptic Ulcer Perforation

Abstract: Objective. Peptic ulcer disease (PUD) in children is an uncommon disorder. An estimated 1.3 percent to 20 percent of people die from perforated peptic ulcers (PPU), a PUD consequence. Using a database, we assess the prevalence and prognosis of PPU in patients. We also do radiological and laparoscopic operations for PPU in young patients. In pediatric patients, sufficient accumulation of knowledge about laparoscopic repair is at the level of case reports. This study aims to assess the results in pediatric cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%